2012
DOI: 10.1258/ijsa.2012.011346
|View full text |Cite
|
Sign up to set email alerts
|

Associations between drug use and risk behaviours for HIV and sexually transmitted infections among female sex workers in Yunnan, China

Abstract: This is a cross-sectional study of 399 subjects conducted to explore the association between drug use and risk behaviour for HIV and sexually transmitted infections (STIs) among female sex workers (FSWs), and also to study the prevalence of HIV/STIs among drug-using FSWs (DUFSWs) and non-DUFSWs in Yunnan province of China. Demographic information, mobility, sexual and drug-using behaviours were collected and subjects were tested for HIV/STIs. Mean age was 27 years (SD = ±7.8) and 94 (23.6%) tested positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The frequency and intensity of drug use are associated with engagement in commercial sex, mostly due to addiction-related financial needs. 60 Drug-using FSWs are more likely to work in low-end sex venues, serve more clients, have a longer history of commercial sex work, and demonstrate riskier sexual behaviours. 15,23,60 A high proportion of FSWs have sexual partners who use drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency and intensity of drug use are associated with engagement in commercial sex, mostly due to addiction-related financial needs. 60 Drug-using FSWs are more likely to work in low-end sex venues, serve more clients, have a longer history of commercial sex work, and demonstrate riskier sexual behaviours. 15,23,60 A high proportion of FSWs have sexual partners who use drugs.…”
Section: Discussionmentioning
confidence: 99%
“…60 Drug-using FSWs are more likely to work in low-end sex venues, serve more clients, have a longer history of commercial sex work, and demonstrate riskier sexual behaviours. 15,23,60 A high proportion of FSWs have sexual partners who use drugs. 23 STIs are reportedly common in FSWs who use drugs and may facilitate the transmission of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high prevalence of HIV infection among FSW coupled with prevailing commercial sex transactions fuels a rapid increase of the heterosexual transmission of HIV in China (Chen, Peeling, Yin, & Mabey, 2011; Cohen, Ping, Fox, & Henderson, 2000). Existing studies have documented unprotected sex (Zhang, Li, Hong, Zhou, et al, 2012), injection drug use (Yao et al, 2012), partner violence (Zhang, Li, Hong, Chen, et al, 2012), infections of other STD (Parish et al, 2003), and no HIV testing (Hong et al, 2012) as risk factors for HIV infection and transmission among this at-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that drug-using sex workers were about half as likely to use condoms as those who did not use drugs (MAP, 2005). Strong relationships between sex work and drug abuse have been found, with an increased risk of contracting HIV and other STIs (Yao et al, 2012), and even with being victims of sexual and physical abuse (Ulibarri, Strathdee &, Patterson, 2010). There is a need to put culturally-appropriate interventions in place, which take advantage of the existing health-related resources and infrastructures.…”
Section: Discussionmentioning
confidence: 99%